Déborah González/Helena Bermúdez Sabel (Eds.): Humanidades Digitales: Miradas hacia la Edad Media. Berlin/Boston: De Gruyter, 2019, 259 pp. ISBN: 978-3-11-058541-4. - Kawasaki, Yoshifumi (Philologia Hispalensis, 2021)
Reseña de la obra de Déborah González/Helena Bermúdez Sabel (Eds.): Humanidades Digitales: Miradas hacia la Edad Media. Berlin/Boston: De Gruyter, 2019.